Analysis and Comparison of the predictive Values of various Frailty-, Comorbidity-, and Activity-of-daily life-Appliances for One-Year Mortality in inpatient geriatric Patients - Ritt, M.; Ritt, J. I.; Sieber, Cornel; Gaßmann, Karl-Günter (SPRINGER HEIDELBERG, 2018)

Analysis of Risks with regard to Malnutrition in hospitalized elderly Ppatients on the basis of different Screening Tools - Christner, S.; Ritt, M.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter (Zeitschrift für Gerontologie und Geriatrie, 2015)

Analysis of Rockwood et Al's Clinical Frailty Scale and Fried et Al's Frailty Phenotype as Predictors of Mortality and Other Clinical Outcomes in Older Patients Who Were Admitted to a Geriatric Ward - Ritt, M.; Schwarz, C.; Kronawitter, V.; Delinic, A.; Bollheimer, Cornelius; Gaßmann, Karl-Günter; Sieber, Cornel (Journal of Nutrition, Health & Aging, 2015)
There are few data regarding the accuracy of short frailty tools as predictors of mortality and other clinical outcomes of older patients admitted to a geriatric ward. We therefore analyzed the accuracy of Rockwood et al's Clinical Frailty Scale and an easy and quick to perform operationalization of Fried et al's frailty phenotype, as predictors of mortality and other clinical outcomes in our cohort of patients.Prospective analysis with a follow-up period of 6 months.307 patients who were 65 years of age or older were included in the study. The patients were assessed in terms of the two frailty measures during their stay in a geriatric ward.The Clinical Frailty Scale and the frailty phenotype were both suitable for differentiating between patients who died due to any cause from those who survived during follow-up (primary outcome) (area under the ROC curves (AUC) values 0.867 (95% CI 0.807-0.926), p<0.001 and 0.754 (95% CI 0.688-0.821), p<0.001, respectively). Regarding the secondary outcomes: 1. unplanned admission to hospital and 2. a fall during follow-up, the Clinical Frailty Scale discriminated or tended to discriminate between patients to whom these criteria applied and those to whom they did not (AUC=0.569 (95% CI 0.502-0.636), p=0.046 and AUC=0.574 (95% CI 0.501-0.647), p=0.071, respectively). The frailty phenotype did not show such a differentiation when applied to secondary outcomes (AUC=0.500 (95% CI 0.432-0.568), p=0.994 and AUC=0.518 (95% CI 0.439-0.598), p=0.658, respectively).Both short frailty instruments are suitable predictors of mortality in older patients who were admitted to a geriatric ward. The Clinical Frailty Scale, but not the frailty phenotype, predicted at least some of the secondary outcomes, i.e., the outcome unplanned admission to hospital during follow-up.
EVALuna2:10581

A prospective community-based study of stroke in Germany - The Erlangen Stroke Project (ESPro): Incidence and case fatality at 1, 3, and 12 months - Kolominsky-Rabas, Peter; Sarti, Cinzia; Heuschmann, Peter U.; Graf, Christian; Siemonsen, Sven; Neundörfer, Bernhard; Katalinic, Alexandar; Lang, Erich; Gaßmann, Karl-Günter; Von Stockert, Theodor Ritter (Stroke, 1998)
Background and Purpose - In Germany, basic data on stroke morbidity are lacking. If a population-based register in former East Germany is excluded, only routine mortality statistics have thus far provided information on epidemiology of stroke. Therefore, a population-based register of stroke was set up in Southern Germany to determine incidence and case fatality in a defined German population. Methods - The Erlangen Stroke Project (ESPro) is a prospective community-based study among the 101 450 residents of the city of Erlangen, Bavaria, Germany. Standard definitions and overlapping case- finding methods were used to identify all cases of first-ever stroke in all age-groups, occurring in the 2 years of registration (April 1, 1994, to March 31, 1996). All identified cases of first-ever strokes were followed up at 3 and 12 months from onset. Results - During 2 years of registration, 354 first-ever-in-a-lifetime strokes (FELS) were registered. The diagnosis and stroke type were confirmed by CT scan in 95% of cases. Fifty-one percent of all FELS occurred in the age group ≥75 years of age. The crude annual incidence rate was 1.74 per 1000 (1.47 for men and 2.01 for women). After age-adjustment to the European population, the incidence rate was 1.34 per 1000 (1.48 for men and 1.25 for women). The annual crude incidence rate of cerebral infarction was 1.37/1000, intracerebral hemorrhage 0.24/1000, subarachnoid hemorrhage 0.06/1000, and unspecified stroke 0.08/1000. Overall case fatality at 28 days was 19.4%, at 3 months it was 28.5%, and at 1 year 37.3%. Conclusions - The first prospective community-based stroke register including all age groups in Germany revealed incidence rates of stroke similar to those reported from other population-based studies in western industrialized countries, but lower than that observed in former East Germany.
Created from Fastlane, Scopus look-up
Keywords: Epidemiology; Germany; Incidence; Mortality; Prognosis

Association of the Change of a Frailty Index based on Routine-Laboratory Parameters during Hospitalization of acute geriatric Patients with 6-Month and 1-Year Mortality - Jaeger, J.; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, M. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Changes of a frailty index based on common blood and urine tests during a hospital stay on geriatric wards predict 6-month and 1-year mortality in older people - Jaeger, Jakob; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, Martin (Clinical Interventions in Aging, 2019)
Background: We aimed to evaluate the abilities of a 21-item frailty index based on laboratory blood and urine tests (FI-Lab21) assessed at different points in time, ie, at admission to hospital (FI-Lab21(admission)) and before discharge from hospital (FI-Lab21(discharge)), and the change of the FI-Lab21 during the hospital stay to predict 6-month and 1-year mortality in hospitalized geriatric patients.
CRIS-Team WoS Importer:2019-03-15

Comparing the predictive accuracy of frailty, comorbidity, and disability for mortality: a 1-year follow-up in patients hospitalized in geriatric wards - Ritt, Martin; Ritt, Julia Isabel; Sieber, Cornel; Gaßmann, Karl-Günter (Clinical Interventions in Aging, 2017)
Background: Studies evaluating and comparing the power of frailty, comorbidity, and disability instruments, together and in parallel, for predicting mortality are limited.Objective: This study aimed to evaluate and compare the measures of frailty, comorbidity, and disability in predicting 1-year mortality in geriatric inpatients.Design: Prospective cohort study.Patients and setting: A total of 307 inpatients aged >= 65 years in geriatric wards of a general hospital participated in the study.Measurements: The patients were evaluated in relation to different frailty, comorbidity, and disability instruments during their hospital stays. These included three frailty (the seven-category Clinical Frailty Scale [CFS-7], a 41-item frailty index [FI], and the FRAIL scale), two comorbidity (the Cumulative Illness Rating Scale for Geriatrics [CIRS-G] and the comorbidity domain of the FI [Comorbidity-D-FI]), and two disability instruments (disability in basic activities of daily living [ADL-Katz] and the instrumental and basic activities of daily living domains of the FI [IADL/ADL-D-FI]). The patients were followed-up over 1 year.Results: Using FI, CIRS-G, Comorbidity-D-FI, and ADL-Katz, this study identified a patient group with a high (>= 50%) 1-year mortality rate in all of the patients and the two patient subgroups (ie, patients aged 65-82 years and >= 83 years). The CFS-7, FI, FRAIL scale, CIRS-G, Comorbidity-D-FI, and IADL/ADL-D-FI (analyzed as full scales) revealed useful discriminative accuracy for 1-year mortality (ie, an area under the curve >0.7) in all the patients and the two patient subgroups (all P<0.001). Thereby, CFS-7 (in all patients and the two patient subgroups) and FI (in the subgroup of patients aged >= 83 years) showed greater discriminative accuracy for 1-year mortality compared to other instruments (all P<0.05).Conclusion: All the different instruments emerged as suitable tools for risk stratification in geriatric inpatients. Among them, CFS-7, and in those patients aged >= 83 years, also the FI, might most accurately predict 1-year mortality in the aforementioned group of individuals.
Keywords: frailty; comorbidity; disability; hospitalized geriatric patients; older people; health status; survival

Evaluation of the nutritional status of older hospitalised geriatric patients: a comparative analysis of a Mini Nutritional Assessment (MNA) version and the Nutritional Risk Screening (NRS 2002) - Christner, S.; Ritt, M.; Volkert, Dorothee; Wirth, Rainer; Sieber, Cornel; Gaßmann, Karl-Günter (Journal of Human Nutrition and Dietetics, 2016)
BackgroundThe present study aimed to evaluate a short-form (MNA-SF) version of the Mini Nutritional Assessment (MNA), in which some of the items were operationalised, based on scores from tools used for a comprehensive geriatric assessment, as a method for analysing the nutritional status of hospitalised geriatric patients. We compared this MNA-SF version with the corresponding MNA long-form (MNA-LF) and Nutritional Risk Screening 2002 (NRS 2002) in terms of completion rate, prevalence and agreement regarding malnutrition and/or the risk of this.MethodsIn total, 201 patients aged 65years who were hospitalised in geriatric wards were included in this analysis.ResultsThe MNA-SF, MNA-LF and NRS 2002 were completed in 98.0%, 95.5% and 99.5% of patients (P=0.06), respectively. The MNA-SF, MNA-LF and NRS 2002 categorised 93.4%, 91.1% and 66.0% of patients as being malnourished or at risk of being malnourished (P<0.001). Agreement between the MNA-SF and MNA-LF was substantial (=0.70, P<0.001). No agreement between the MNA-SF and NRS 2002 was found (=-0.12, P<0.001). Interestingly, NRS 2002 part 1 (prescreening) revealed a false negative rate of 21.0% (only in patients aged 70years who showed moderate disease severity) in relation to the NRS 2002 part 2.ConclusionsThe MNA-SF version emerged as a useful tool for evaluating the nutritional status of hospitalised geriatric patients. The NRS 2002 part 1 showed limited value as a prescreening aid in relation to the NRS 2002 part 2 in the same group of patients.
Keywords: clinical nutrition; malnutrition; nutrition screening; nutritional assessment

Frail older individuals maintaining a steady standing position: Associations between sway measurements with frailty status across four different frailty instruments - Schuelein, Samuel; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, Martin (Clinical Interventions in Aging, 2020)
Objective: An analysis of the relationships between static equilibrium parameters and frailty status and/or severity across four different frailty measures. Design: Cross-sectional analysis. Setting: Geriatric wards of a general hospital. Participants: One hundred twenty-three geriatric inpatients comprising 70 women (56.5%) and 53 men (42.7%) with an age range of 68–95 years. Methods: The variation in the center of pressure (CoP), ie, the length of sway, the area of sway, and the mean speed, was assessed for different positions/tasks: 1) wide standing with eyes open (WSEO); 2) wide standing with eyes closed (WSEC); 3) narrow standing with eyes open (NSEO) and 4) narrow standing with eyes closed (NSEC), using a force plate. Frailty status and/or frailty severity were evaluated using the frailty phenotype (FP), the clinical frailty scale (CFS), the 14-item frailty index based on a comprehensive geriatric assessment (FI-CGA), and a 47-item frailty index (FI). Results: WSEO length of sway (FP, CFS, FI-CGA, FI), WSEO area of sway (FP, CFS, FI-CGA, FI), and WSEO mean speed (FP, CFS, FI-CGA, FI), WSEC length of sway (FP, FI-CGA, FI), WSEC area of sway (FP, FI-CGA, FI) and WSEC mean speed (FI-CGA, FI), NSEO length of sway (FP, FI-CGA, FI), NSEO area of sway (FP, CFS, FI-CGA, FI), and NSEO mean speed (FP, CFS, FI-CGA, FI), NSEC length of sway (FI-CGA, FI), NSEC area of sway (FI-CGA, FI) and NSEC mean speed (FI-CGA, FI) were associated with the frailty status and/or severity across the four different frailty instruments (all p < 0.05, respectively). Conclusion: Greater fluctuations in CoP with increasing frailty status and/or severity were a uniform finding across various major frailty instruments.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Balance quality parameters; Frailty instruments; Older people

Frailty as clinically relevant Parameters in elderly Patients with arterial Hypertension - the FOHYP Study: Rationale and Study Design - Ritt, M.; Schwarz, C.; Bollheimer, Cornelius; Schmieder, Roland; Gaßmann, Karl-Günter; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2013)

Geriatric Assessments Can Predict Functional Outcome and Mortality after Urological Tumor Surgery - Kahlmeyer, Andreas; Fiebig, Christian; Müller, Marco; Kraulich, Matthias; Brendel-Suchanek, Jonas; Kunath, Frank; Wach, Sven; Goebell, Peter; Ritt, Martin; Gaßmann, Karl-Günter; Wullich, Bernd (Urologia Internationalis, 2021)
Introduction: Older patients undergoing major urological tumor surgery are at severe risk of functional deterioration, complications, and mortality. We prospectively evaluated geriatric assessment tools and developed a novel easy-to-use assessment tool for clinical use. Methods: In 159 patients, geriatric assessment tools were used prior to cystectomy, prostatectomy, and renal tumor surgery, and their peri- and postoperative courses were recorded. Using all the tests, a short and easy-to-use assessment tool was developed, and nomograms were generated to predict functional outcomes and mortality. Results: Of all the patients, 13.8% underwent radical cystectomy, 37.7% underwent radical prostatectomy, and 48.4% underwent tumor surgery of the kidney at the age of 70 years or older. The average age was 75.6 years. Incomplete functional recovery at day 30 and day 180 was observed in 37.7% and 36.1% of the patients, respectively, and incomplete functional recovery was associated with impaired mobility, previous care dependency, frailty, comorbidities, and a high ASA score. The only predictor for high-grade complications was comorbidities, whereas mortality was associated with the geriatric screening tool scores, impaired mobility, preoperative care dependency, and comorbidities. The Erlangen Index (EI), a combination of the selected assessment tools, showed a good prediction of early (p = 0.002) and medium-term (p = 0.002) functional outcomes and mortality (p = 0.001). Conclusion: Our prospective evaluation confirms the high risk of incomplete functional recovery, high-grade complications, and mortality in older patients undergoing major urological tumor surgery. The EI is an easy-to-use preoperative assessment tool and therefore should be used in preoperative patient counseling.
CRIS-Team WoS Importer:2021-10-01

High-technology based gait assessment in frail people: Associations between spatio-temporal and three-dimensional gait characteristics with frailty status across four different frailty measures - Ritt, M.; Schuelein, S.; Lubrich, H.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter (Journal of Nutrition, Health & Aging, 2017)
We analyzed associations between a battery of gait characteristics and frailty status across four different frailty instruments in old patients.Cross-sectional study.Geriatric wards of a general hospital.123 hospitalized patients aged ae65 years.Spatio-temporal and three-dimensional gait characteristics were assessed by an electronic walkway and a shoe-mounted, inertial sensor-based mobile gait analysis system. Frailty status was assessed by the frailty phenotype (FP), Clinical Frailty Scale (CFS), frailty index (FI), and frailty index based on a comprehensive geriatric assessment (FI-CGA).A reduction in walking speed (FP, FI, FI-CGA), stride length (FP, FI, FI-CGA), maximum toe clearance (FP, CFS, FI, FI-CGA), toe off angle (FP, CFS, FI, FI-CGA), heal strike angle (FI-CGA) and greater stride length variability (FP, CFS, FI, FI-CGA), stride time variability (FP, FI), double support time (FP, FI), and stride width (CFA, FI-CGA) were associated with frailty status across the four frailty instruments (all P < 0.05, respectively). Walking speed (FP, CFS, FI, FI-CGA), stride length (FP, CFS, FI, FI-CGA), maximum toe clearance (FP, CFS, FI, FI-CGA), toe off angle (FP, CFS, FI, FI-CGA), heal strike angle (FP, FI), stride length variability (CFS, FI, FI-CGA), stride time variability (FI), double support time (FP), and stride width (FP, CFS, FI) were related with frailty severity across the four frailty instruments independent of age and sex (all P adjusted < 0.05, respectively).Gait changes in frail patients include more than solely a reduction in walking speed.
Keywords: Frailty; gait characteristics; older people

Identification of diagnosis-related contraindications based on the medication plan alone - Andrikyan, Wahram; Then, Melanie; Gaßmann, Karl-Günter; Tuemena, T.; Dürr, Pauline; Fromm, Martin; Maas, Renke (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-15

Implementation and results of a geriatric medication database (Aufbau und Ergebnisse einer Geriatrischen Medikamentendatenbank) - Gaßmann, Karl-Günter; Tümena, T.; Schlee, S.; Garner, C.; Kieslich, B.; Kraft, J.; Schwab, M.; Sieber, Cornel; Stobbe, A.; Trögner, J. (Zeitschrift für Gerontologie und Geriatrie, 2012)
Keywords: Geriatrics; Inappropriate prescription; Geriatric assessment; Multimorbidity; Polypharmacy

Initiative patient-oriented Geriatric Medicine (IPA (R))"Treat Wisely" - Expert Consensus on Dealing with Polypharmacy - Metz, B. R.; Frohnhofen, H.; Gaßmann, Karl-Günter; Johnsen, M.; Schwab, M.; Grabenbauer, C. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

Mobile Stride Length Estimation with Deep Convolutional Neural Networks. - Hannink, Julius; Kautz, Thomas; Pasluosta, Cristian Federico; Barth, Jens; Schülein, Samuel; Gaßmann, Karl-Günter; Klucken, Jochen; Eskofier, Björn (IEEE Journal of Biomedical and Health Informatics, 2018)

Multicentric validation of a comprehensive geriatric assessment to predict functional outcome and mortality following urooncological operations - Fiebig, Christian; Kahlmeyer, Andreas; Bannert, Hannes; Taubert, Helge; Wach, Sven; Koneval, Lukas; Graf, Sebastian; Folchini, Decio Maria; Alalem, Sameh; Gaßmann, Karl-Günter; Wullich, Bernd (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Operationalizing a frailty index using routine blood and urine tests - Ritt, Martin; Jaeger, Jakob; Ritt, Julia Isabel; Sieber, Cornel; Gaßmann, Karl-Günter (Clinical Interventions in Aging, 2017)
Background: Uncomplicated frailty instruments are desirable for use in a busy clinical setting. The aim of this study was to operationalize a frailty index (FI) from routine blood and urine tests, and to evaluate the properties of this FI compared to other frailty instruments.Materials and methods: We conducted a secondary analysis of a prospective cohort study on 306 patients aged >= 65 years hospitalized on geriatric wards. An FI comprising 22 routine blood parameters and one standard urine parameter (FI-Lab), a 50-item FI based on a comprehensive geriatric assessment (FI-CGA), a combined FI (FI-combined [items from the FI-Lab + others from the FI-CGA]), the Clinical Frailty Scale, rule-based frailty definition, and frailty phenotype were operationalized from data obtained during patients' hospital stays (ie, before discharge [baseline examination]). Follow-up data were obtained up to 1 year after the baseline examination.Results: The mean FI-Lab score was 0.34 +/- 15, with an upper limit of 0.74. The FI-Lab was correlated with all the other frailty instruments (all P < 0.001). The FI-Lab revealed an area under the receiver-operating characteristic curve (AUC) for 6-month and 1-year mortality of 0.765 (0.694-0.836) and 0.769 (0.706-0.833), respectively (all P < 0.001). Each 0.01 increment in FI-Lab increased the risk (adjusted for age and sex) for 6-month and 1-year mortality by 7.2% and 7.1%, respectively (all adjusted P < 0.001). When any of the other FIs (except the FI-combined) were also included in the models, each 0.01 increment in FI-Lab score was associated with an increase in the risk of 6-month and 1-year mortality by 4.1%-5.4% (all adjusted P < 0.001).Conclusion: The FI-Lab showed key characteristics of an FI. The FI-Lab can be applied as a single frailty measure or in combination with/ in addition to other frailty instruments.
Keywords: older people; hospital; geriatric wards; frailty; risk stratification; mortality

Predictability of a modified Mini- Nutritional- Assessment version on six-month and one-year mortality in hospitalized geriatric patients: a comparative analysis - Becker, Lea; Volkert, Dorothee; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, Martin (Scientific Reports, 2019)
Recently we introduced a modified Mini Nutritional Assessment (MNA) Short Form (MNA-SF) and Long Form (MNA-SF) with operationalization of the ‘mobility’ and ‘neuropsychological problems’ items of the MNA using scores on Barthel Index mobility item and Mini Mental State Examination and Geriatric Depression Scale scores. We have now evaluated the abilities of this modified MNA-SF and MNA-LF to predict mortality in comparison with the standard MNA-SF and MNA-LF and the Nutritional Risk Screening 2002 (NRS 2002) and the Malnutrition Universal Screening Tool (MUST). A prospective analysis was performed in 240 hospitalised geriatric patients aged ≥ 65 years. Malnutrition and/or malnutrition risk were assessed using the modified MNA-SF and MNA-LF, the standard MNA-SF and MNA-LF, and the NRS 2002 and MUST. The modified MNA-SF and MNA-LF and the standard MNA-SF and MNA-LF assessments (all p < 0.05), but not NRS 2002 or MUST (all p ≥ 0.05), predicted six-month and/or one-year mortality. Prediction of six-month and/or one-year mortality by the modified MNA-SF was comparable with predictions by the standard MNA-SF and MNA-LF (all p ≥ 0.05). The modified MNA-LF showed better prediction of six-month and one-year mortality than the standard MNA-SF and MNA-LF (all p < 0.05). The modified MNA-LF (all adjusted p < 0.05), but none of the other instruments (all adjusted p ≥ 0.05), predicted six-month and one-year mortality independently of age, sex, frailty, comorbidity and ADL disability burden. The modified MNA-SF and MNA-LF emerged as potentially valuable tools for predicting mortality in patients hospitalised on geriatric wards.
CRIS-Team Scopus Importer:2019-07-02

Preoperative geriatric assessment to predict functional outcome after major urologic operations: Results from a multicenter study - Graf, Sebastian; Lutz, Jakob; Koneval, Lukas; Kalogirou, Charis; Weiß, Sarah Christiane; Bannert, Hannes; Taubert, Helge; Wach, Sven; Gaßmann, Karl-Günter; Wullich, Bernd; Fiebig, Christian (Ejso, 2024)
Introduction: Major urological tumor surgery entails a severe risk of unexpected adverse events, persistent functional deterioration, and death in older patients. The Erlangen Index (EI) geriatric assessment tool has previously been shown to predict incomplete functional recovery following major urological tumor surgery in an elderly patient collective. We prospectively evaluated assessment tools including EI in a multicenter setting. Materials and methods: A total of 340 patients over the age of 65 were assessed prospectively before and after cystectomy, prostatectomy, or renal tumor surgery at three academic centers in Germany and Austria. Endpoints were long-term functional deterioration (Activities of daily living (ADL) measured by Barthel-Index) at day 30 and day 180, and mortality at day 180. Results: In this study 58 (17.0 %) patients underwent cystectomy, 140 (41.2 %) prostatectomy and 142 (41.8 %) a kidney tumor operation. Mean age was 74.8 years. ADL impairment as a measure of incomplete recovery at day 30 and 180 after surgery were recorded in 47.6 % and 37.4 % of cases, respectively. The EI showed good sensitivity for mortality at day 180 (reference cohort: 85 %, validation center 1: 100 %, validation center 2: 50 %) and for ADL impairment at day 180 (reference cohort 75.4 %, validation center 1 72.3 %, validation center 2 83.3 %). Conclusion: Elderly patients with a poor performance status have a high risk of persistent functional deterioration. Data from this multicenter external validation trial confirms the EI as an accurate and reliable tool to identify patients with high risk of mortality or persistent postoperative functional impairment.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Erlangen index; Frailty; Functional impairment; Geriatric assessment; Oncological surgery; Urological surgery

Prospective longitudinal Analysis of the Clinical Frailty Scale as prognostic Parameters in elderly Patients with arterial Hypertension - Kronawitter, V.; Radi, K. H.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, M. (Zeitschrift für Gerontologie und Geriatrie, 2015)

Renal Function and the extended Frailty Construct according to Rockwood et al. in elderly hospitalized Patients - Ritt, M.; Schwarz, C.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter (Zeitschrift für Gerontologie und Geriatrie, 2015)

Renal Function and the extended Frailty Construct according to Rockwood et al. in elderly hospitalized Patients - Ritt, M.; Schwarz, C.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter (Zeitschrift für Gerontologie und Geriatrie, 2015)

Significance of frailty for predicting adverse clinical outcomes in different patient groups with specific medical conditions - Ritt, Martin; Gaßmann, Karl-Günter; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2016)
Frailty is a major health burden in an aging society. It constitutes a clinical state of reduced physiological reserves that is associated with a diminished ability to withstand internal and external stressors. Frail patients have an increased risk for adverse clinical outcomes, such as mortality, readmission to hospital, institutionalization and falls. Of further clinical interest, frailty might be at least in part reversible in some patients and subject to preventive strategies. In daily clinical practice older patients with a complex health status, who are mostly frail or at least at risk of developing frailty, are frequently cared for by geriatricians. Recently, clinicians and scientists from other medical disciplines, such as cardiology, pulmonology, gastroenterology, nephrology, endocrinology, rheumatology, surgery and critical care medicine also discovered frailty to be an interesting instrument for risk stratification of patients, including younger patients. In this review we highlight the results of recent studies that demonstrated the significance of frailty to predict adverse clinical outcomes in patients with specific medical conditions, such as cardiac, lung, liver and kidney diseases as well as diabetes mellitus, osteoarthritis, trauma patients, patients undergoing surgery and critically ill patients. Multiple studies in patients with the aforementioned specific medical conditions could be identified demonstrating a predictive role of frailty for several adverse clinical outcomes. The association between frailty and adverse clinical outcomes reported in these studies was in part independent of several major potential confounder factors, such as age, sex, race, comorbidities and disabilities and were also detected in younger patients.
Keywords: Frail elderly; Clinical frailty scale; Phenotype; Comorbidities; Mortality

Use of medication data alone to identify diagnoses and related contraindications: Application of algorithms to close a common documentation gap - Andrikyan, Wahram; Then, Melanie; Gaßmann, Karl-Günter; Tuemena, Thomas; Dürr, Pauline; Fromm, Martin; Maas, Renke (British Journal of Clinical Pharmacology, 2022)
Aims: Automated checks for medication-related problems have become a cornerstone of medication safety. In many clinical settings medication checks remain confined to drug–drug interactions because only medication data are available in an adequately coded form, leaving possible contraindicated drug–disease combinations unaccounted for. Therefore, we devised algorithms that identify frequently contraindicated diagnoses based on medication patterns related to these diagnoses. Methods: We identified drugs that are associated with diseases constituting common contraindications based on their exclusive use for these conditions (such as allopurinol for gout or salbutamol for bronchial obstruction). Expert-based and machine learning algorithms were developed to identify diagnoses based on highly specific medication patterns. The applicability, sensitivity and specificity of the approach were assessed by using an anonymized real-life sample of medication and diagnosis data excerpts from 3506 discharge records of geriatric patients. Results: Depending on the algorithm, the desired focus (i.e., sensitivity vs. specificity) and the disease, we were able to identify the diagnoses gout, epilepsy, coronary artery disease, congestive heart failure and bronchial obstruction with a specificity of 44.0–99.8% (95% CI 41.7–100.0%) and a sensitivity of 3.8–83.1% (95% CI 1.0–86.1%). Using only medication data, we were able to identify 123 (51.3%) of 240 contraindications identified by experts with access to medication data and diagnoses. Conclusion: This study provides a proof of principle that some key diagnosis-related contraindications can be identified based on a patient's medication data alone, while others cannot be identified. This approach offers new opportunities to analyse drug–disease contraindications in community pharmacy or clinical routine data.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Anatomical Therapeutic Chemical Classification System; ATC; contraindication; ICD; International Statistical Classification of Diseases and Related Health Problems; machine learning; medication error; medication safety; Prescribing Information; Summary of Product Characteristics